2013
DOI: 10.1007/s00240-013-0581-8
|View full text |Cite|
|
Sign up to set email alerts
|

Positive stone culture is associated with a higher rate of sepsis after endourological procedures

Abstract: The purpose of this study was to determine if there is a correlation between urine and/or stone cultures with postoperative sepsis in patients treated for renal and ureteral calculi. Three hundred and twenty-eight consecutive patients who underwent percutaneous nephrolithotomy (PCNL) or ureteroscopy from 2006 to 2009 were identified, all of whom had a stone culture obtained during surgery. All had a preoperative urine culture. Two hundred and seventy-four underwent ureteroscopy and 54 PCNL. All patients had ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 10 publications
4
33
0
5
Order By: Relevance
“…Infection complication is also a common and troublesome issue with PCNL. Many factors such as diabetes, positive preoperative urine culture, infection stones, staghorn stones, multiple punctures, and length of operative time had all been proven to be predictors for postoperative infection complications [13,14]. The present study showed that there was no significant difference in the rate of infection complication, including SIRS and septic shock, between both approaches.…”
Section: Discussionmentioning
confidence: 68%
“…Infection complication is also a common and troublesome issue with PCNL. Many factors such as diabetes, positive preoperative urine culture, infection stones, staghorn stones, multiple punctures, and length of operative time had all been proven to be predictors for postoperative infection complications [13,14]. The present study showed that there was no significant difference in the rate of infection complication, including SIRS and septic shock, between both approaches.…”
Section: Discussionmentioning
confidence: 68%
“…Though the 2005 guideline from Infectious Diseases Society of America recommends routine treatment of asymptomatic bacteriuria in patients undergoing urological procedures 24 , recent data from patients undergoing stone surgery have questioned the value of preoperative urine culture, as asymptomatic bacteriuria is a poor predictor of postoperative infection. 25 Furthermore, several studies have shown that treatment of asymptomatic bacteriuria in bladder cancer patients undergoing outpatient urological procedures (ie. cystoscopy and intravesical therapy) is unnecessary as these patients did not have an increased risk of UTI.…”
Section: Discussionmentioning
confidence: 99%
“…However, the other 2 patients tested positive for PCN urine culture while negative for bladder urine culture. Eswara et al [12] reported that-among readmitted patients who developed sepsis after having undergone treatment for a stone-there was only 64% correspondence between whether both their stone culture and their urine culture tested positive. Additionally, another previous study reported that stone culture results were better correlated with pelvic, rather than bladder, urine culture results [13].…”
Section: Discussionmentioning
confidence: 99%